Doctoral supervision and research culture : what we know, what works and why - Clegg, Karen (Routledge, 2024)
"Drawing on original survey data, reflective accounts, and case studies of supervisory practice in different disciplines, Doctoral Supervision and Research Culture explores the supervisor experience and demonstrates the craft, compassion and consistency required of supervisors in responding to different researcher's needs. Based on empirical data and using the voice of research supervisors, the authors throw a spotlight on the challenges and opportunities supervisors face in supporting doctoral researchers through to successful PhD completion. This book acts as an invitation to institutions, funders, industry and academics to review what, and how they support PhD provision and to elevate the status of supervision practice. It shows how research cultures - disciplinary, institutional and individual - affect the supervisory experience and highlight the challenges that supervisors face, as well as the rewards that successful supervisory relationships bring. It is also a celebration of the contribution that doctoral researchers and all those who support research make to society. Designed to provide opportunities for sharing of practice across disciplines and the sector, Doctoral Supervision and Research Culture will be of interest to both new and experienced supervisors, to staff and researcher developers in institutions, and to funders, policy makers and senior management in universities who seek to improve and enhance the supervisory experience for all agents"--